A comparison between experimental and predicted flow profiles beneath a semi-confined axisymmetric impinging jet - Cheong, C; Ireland, P; Ashforth-Frost, S (2003)
Theoretical predictions have been compared with experiment for a single semi-confined impinging jet. The turbulent air jet discharged at Re = 20 000 and impinged at nozzle-to-plate spacings (z/d) of 2 and 6.5. Experimental velocity profiles were obtained using hot-wire anemometry. Theoretical velocity profiles were derived using stagnation three-dimensional flow model and viscous flow model for an axisymmetric case. For z/d = 2, velocity profiles in the inviscid region of the near wall flow can be predicted accurately using the stagnation flow model. As the edge of the jet is approached, the flow becomes complex and, as expected, cannot be predicted using the model. Prediction of boundary layer profiles using the viscous flow solution for an axisymmetric case is also reasonable. For z/d = 6.5, the developing impinging jet is essentially turbulent on impact and consequently predictions of near wall flow field, using both the theoretical models, are inappropriate.